Peanut butter confirmed as the source in a case of infant botulism, United Kingdom, 2024 - Gauri Godbole (Eurosurveillance)
A 6-month-old infant was hospitalised with suspected infant botulism after being given peanut butter to reduce their risk of developing peanut allergy. Clostridium botulinum type A was detected in their faeces and the peanut butter by PCR and culture. Whole genome sequencing confirmed identical strains, identifying the peanut butter as the source of infection. The infant was treated with human-derived antitoxin Botulism Immune Globulin Intravenous (Human) (BIG-IV) and recovered well. This case highlights potential botulism risk with early peanut introduction.